Antifungal Potential of Melastoma malabathricum L. Leaf Extract against Candida albicans: A Phytochemical Approach - Mayasari, Dian; Meiliani, Siska (Universitas Muhammadiyah Surakarta, 2025)
Candida species are opportunistic fungi, capable of causing acute and chronic infections in the gastrointestinal tract, vagina, and oral mucosa among which Candida albicans is the most important species. Melastoma malabathricum L. is one of the most important traditional medicinal plants in Sumatera Island, Indonesia used to treat infectious diseases. The main of this work was to evaluate phytochemical screening of ethanol extract of M. malabathricum leaf, qualitative analysis of mixture compounds by TLC analysis and investigation antifungal activity against C. albicans. The antifungal activity of plant extract at concentrations of 20%, 40%, 60% and 80% were assessed using agar-well diffusion method. Flavonoids, saponins and tannins were secondary metabolites found in ethanol extract. The extract of M. malabathricum leaf formed a zone of inhibition of 6.45 ± 0.002, 6.35 ± 0.023, 6.30 ± 0.050 at concentrations of 20%, 40%, 60%, respectively. In conclusion, M. malabathricum leaf had weak antifungal activity. In addition, ethanolic extract had a variety of secondary metabolites that possibly have antifungal activities. Thus, the present findings support the folklore use of M. malabathricum for the treatment of different fungal infections.